Agriculture and the Environment - Edward Madigan; Morris, Scott Edward; Chelsea House Publishers (New York : Chelsea House Publishers, 1993)
Eighteen map spreads show the world's vegetation, both natural and cultivated.
Includes glossary and index.
Includes bibliography: p. 43.
Keywords: Plant distribution -- Maps; Agriculture -- Maps; World atlases; Children's maps